PENGARUH AUDIT TENURE, AUDITOR INDUSTRY SPECIALISATION, AUDIT FIRM SIZE TERHADAP AUDIT QUALITY - Stephanie Angeline; Susanto Salim (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This research aims to examine the relationship of Audit Tenure, Auditor Industry Specialisation, and Audit Firm Size to Audit Quality. The objective is to analyze the direction and influence between Audit Tenure, Auditor Industry Specialisation and Audit Firm Size to Audit Quality. This study uses a infrastructure company listed on IDX during 2016-2019 as a population. Sample is selected by purposive sampling technique. Out of 77 infrastructure companies, there are 31 infrastructure companies that have passed the research criteria. Data is taken from www.idx.co.id. In this research data processing using Microsoft Excel and program Statistical Product and Service Solution (SPSS) for windows version 25. The results of this study indicate that audit tenure has not a significant negative effect on audit quality, auditor industry specialisation has not a significant positive effect on audit quality, and audit firm size has a significant negative effect on audit quality on the infrastructure company. The implication of this study is the need to add more independent or control variable that is related to audit quality so each variable can define strongly to audit quality.